Математична модель відтворення і задания контрольного об’єму газу установками дзвонового типу - Вощинський, В. (Видавництво Національного університету “Львівська політехніка”, 2004)
The mathematical modelling of reproduction and task of control volume of gas by bell installations is carried out. The mathematical model of control volume of gas supersed by a bell is received at constant pressure. The influence of change of pressure under a bell on control volume of gas is investigated. The dependence is received which determines change of control volume from change of pressure under a bell.
Keywords: 389.681.121.089